Code of practice on tobacco control for oral health organisations - POLICY STATEMENT, FDI; PTS, STANOWISKO (Journal of Stomatology, 2015)
In order to contribute actively to the reduction of tobacco consumption and include tobacco control in the public health agenda at national, regional and global levels, it is recommended that oral health organisations will:1. Encourage and support their members to be role models by not using tobacco and by promoting a tobacco-free culture.2. Assess and address the tobacco consumption patterns and tobacco-control attitudes of their members through surveys and the introduction of appropriate policies.3. Make their own organisations’ premises and events tobacco-free and encourage their members to do the same.4. Include tobacco control in the agenda of all relevant health-related congresses and conferences.5. Advise their members to routinely ask patients and clients about tobacco consumption and exposure to tobacco smoke – using evidence- based approaches and best practices – give advice on how to quit smoking and ensure appropriate follow-up of their cessation goals.6. Influence health institutions and educational centres to include tobacco control in their health professionals' curricula, through continued education and other training programmes.7. Actively participate in World No Tobacco Day every 31 May.8. Refrain from accepting any kind of tobacco industry support – financial or otherwise –, and from investing in the tobacco industry, and encourage their members to do the same.9. Whenever possible, organisations will give preference to partners who have a policy indicating that they refrain from accepting any kind of tobacco industry support – financial or otherwise – from investing in the tobacco industry and encourage their members to do the same.10. Prohibit the sale or promotion of tobacco products on their premises, and encourage their members to do the same.11. Actively support governments in the process leading to signature, ratification and implementation of the WHO Framework Convention on Tobacco Control.12. Dedicate financial and/or other resources to tobacco control – including dedicating resources to the implementation of this code of practice.13. Participate in the tobacco-control activities of health professional networks.14. Support campaigns for tobacco-free public places.